2005
DOI: 10.1016/j.cell.2005.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of 5′-Directed Human Mismatch Repair in a Purified System

Abstract: This paper reports reconstitution of 5'-nick-directed mismatch repair using purified human proteins. The reconstituted system includes MutSalpha or MutSbeta, MutLalpha, RPA, EXO1, HMGB1, PCNA, RFC, polymerase delta, and ligase I. In this system, MutSbeta plays a limited role in repair of base-base mismatches, but it processes insertion/deletion mispairs much more efficiently than MutSalpha, which efficiently corrects both types of heteroduplexes. MutLalpha reduces the processivity of EXO1 and terminates EXO1-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
358
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(387 citation statements)
references
References 43 publications
(47 reference statements)
24
358
1
1
Order By: Relevance
“…1 and discussion below), and reconstitutions in the Li and Modrich laboratories of MMR reactions from purified proteins possess many of the key features associated with MMR in vivo (Constantin et al, 2005;Dzantiev et al, 2004;Zhang et al, 2005). These studies were predicated on a large body of earlier work that identified individual components from active fractions of cell extracts and characterized partial reactions (reviewed in Jiricny, 2006).…”
Section: Mutation Avoidance and Post-replication Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and discussion below), and reconstitutions in the Li and Modrich laboratories of MMR reactions from purified proteins possess many of the key features associated with MMR in vivo (Constantin et al, 2005;Dzantiev et al, 2004;Zhang et al, 2005). These studies were predicated on a large body of earlier work that identified individual components from active fractions of cell extracts and characterized partial reactions (reviewed in Jiricny, 2006).…”
Section: Mutation Avoidance and Post-replication Repairmentioning
confidence: 99%
“…These studies were predicated on a large body of earlier work that identified individual components from active fractions of cell extracts and characterized partial reactions (reviewed in Jiricny, 2006). Zhang et al (2005) have demonstrated MMR of a G-T mismatch in 5′-directed repair reactions containing MutSα, MutLα, RPA, EXO1, PCNA, RFC, HMGB1, DNA polymerase δ, and DNA ligase I (Yuan et al, 2004). Substitution of MutSβ for MutSα allowed repair of a 3 nt IDL.…”
Section: Mutation Avoidance and Post-replication Repairmentioning
confidence: 99%
“…In mammals, MMR is mediated by proteins homologous to prokaryotic MMR factors, such as Msh2, Msh3 and Msh6 and MutL homologues (Mlh) 1, Mlh3, postmeiotic segregation increased (Pms)1 and Pms2. Consistent with the role of Msh2-Msh6 as the sensor for single-nucleotide mismatches (Kunkel and Erie, 2005;Zhang et al, 2005), mice deficient in Msh2 and/or Msh6 exhibit an overall decreased frequency of mutations. In these mice, residual mutations show a significantly altered spectrum, with decreased mutations at dA/dT and concurrent increased mutations at dC/dG (Table 2) (Rada et al, 1998;Martin and Scharff, 2002;Martomo et al, 2004;Rada et al, 2004).…”
Section: Error-prone Mmr Amplifies Mutations In the Mutasomesupporting
confidence: 53%
“…The minimal human MMR system was reconstituted from its individual purified components MutSα or MutSβ, MutLα, EXO1, RFC, PCNA, RPA, polymerase-δ and DNA ligase I several years ago [4,5] and has been extensively reviewed [6][7][8][9][10][11]. We shall therefore discuss only the key features of the system and focus on recent work that yielded novel mechanistic insights into this important pathway of DNA metabolism.…”
Section: Repair Of Base/base Mismatches and Idlsmentioning
confidence: 99%